2007
DOI: 10.2215/cjn.00600207
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Lactic Acid Bacteria for Idiopathic Hyperoxaluria

Abstract: Background: Urinary oxalate excretion is an important contributor to calcium oxalate stone formation. Methods of reducing oxalate excretion are not wholly satisfactory, and no controlled trials using them have been performed to prevent stone recurrence. Some lactic acid bacteria can degrade oxalate in vitro. This study sought to reduce urinary oxalate excretion in calcium stone formers with idiopathic hyperoxaluria.Design, setting, participants, and measurements: A randomized, double-blind, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 10 publications
0
54
1
2
Order By: Relevance
“…New approaches such as the use of probiotics like Oxalobacter formigenes, which act as oxalatedegraders, appear to be promising in calcium oxalate stone formers. However, the results are not consistent [114,115] . Future alternative treatments of hyperoxaluria involve upregulation of intestinal secretion through the increase of the anion transporter activity (S1c26a6) [118] .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…New approaches such as the use of probiotics like Oxalobacter formigenes, which act as oxalatedegraders, appear to be promising in calcium oxalate stone formers. However, the results are not consistent [114,115] . Future alternative treatments of hyperoxaluria involve upregulation of intestinal secretion through the increase of the anion transporter activity (S1c26a6) [118] .…”
Section: Resultsmentioning
confidence: 78%
“…However, in vivo results are contradictory. Goldfarb et al [114] found that lactic acid bacteria are ineffective in patients with absorptive hypercalciuria. Effective reduction in urine oxalate excretion was described by Lieske et al [115] in patients with secondary absorptive hyperoxaluria associated with fat malabsorption.…”
Section: Hypocitraturiamentioning
confidence: 99%
“…Recently it has been shown that the gastrointestinal tract presents an alternative route of oxalate elimination, especially under conditions of renal insufficiency [4]. It has also been recognized that an endogenous component of intestinal microflora potentially limits oxalate absorption or enhances its colonic excretion [5,6,7]. Such data open new horizons for pharmacological manipulation of oxalate in the intestine that may affect its systemic balance [3, 5, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, an oxalate-free diet is difficult to achieve and would probably be deficient in essential nutrients. Hence, other approaches to reducing urinary oxalate for management of stone disease have been explored.The discovery of oxalate-degrading bacteria within the human gastrointestinal tract has opened the way to a flurry of research regarding their potential role in reducing urinary excretion of oxalic acid (12,20,21,25,26,30,31,35,40,44,45). The first intestinal oxalate-degrading bacterium to be described was Oxalobacter formigenes, an obligate anaerobe which relies exclusively on oxalate metabolism for energy (2).…”
mentioning
confidence: 99%